The effectiveness of self-differentiation training on family process and marital intimacy in couples with marital conflict - Seyedeh Farzaneh Jafari; Kobra Kazemian Moghaddam; Maryam Gholamzadeh Jofreh (Preventive Care in Nursing and Midwifery Journal)
Background: The rising prevalence of marital conflict and its detrimental impact on individual and family well-being underscores the urgent need for effective interventions. Objectives: This study aimed to investigate the effectiveness of self-differentiation training on family process and marital intimacy in couples with marital conflict. Methods: A quasi-experimental pre-test, post-test, and follow-up design was utilized. The study population comprised all couples residing in Ahvaz, Iran, aged between 20 and 45, who sought divorce counseling at psychological centers in 2023. A convenience sample of 30 couples was recruited. Participants completed the Family Process Scale and the Marital Intimacy Scale at baseline, post-intervention, and a 45-day follow-up assessment. The intervention consisted of eight weekly 90-minute self-differentiation training sessions. Data were analyzed using repeated-measures analysis of variance. Post-hoc comparisons were conducted employing the LSD test. Results: A significant increase in family process scores was observed between the pre-test and post-test assessments among couples experiencing marital conflict (p<0.001). Similarly, significant improvements in marital intimacy were found between the pre-test and both the post-test and follow-up assessments (P<0.001). These sustained effects at follow-up indicate the long-lasting impact of self-differentiation training. Conclusion: Self-differentiation training significantly improved family processes and marital intimacy in couples experiencing conflict, suggesting its effectiveness in addressing the core issues underlying marital discord. Therefore, mental health professionals and family therapists should consider incorporating self-differentiation training into their practice when working with couples experiencing marital conflict, particularly those considering separation or divorce.